2017
DOI: 10.5530/jppcm.2017.3.32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Pharmacist Consultation Visits at Ministry of Health Hospitals in Saudi Arabia: Clinical Pharmacy Services and Pharmacy Workforce

Abstract: Background: Pharmacy practice residency program (PPRG) is one of a major professional degree in Saudi Arabia. The residency is very high demand in the pharmacy market. The clinical pharmacist

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The hospital pharmacists at MOH showed a significant impact on reducing medication errors, improving patient outcomes and avoiding millions of US dollar annually. [32][33][34] The nationality results showed that most of the pharmacists were from Saudi due to the Saudisation plan of MOH. Another parameter of pharmacy workforces could not compare with studies because it missed at MOH statistical books.…”
Section: Discussionmentioning
confidence: 99%
“…The hospital pharmacists at MOH showed a significant impact on reducing medication errors, improving patient outcomes and avoiding millions of US dollar annually. [32][33][34] The nationality results showed that most of the pharmacists were from Saudi due to the Saudisation plan of MOH. Another parameter of pharmacy workforces could not compare with studies because it missed at MOH statistical books.…”
Section: Discussionmentioning
confidence: 99%
“…After starting clinical pharmacy services at MOH, several studies conducted to show the benefit the services at overall the Kingdom of Saudi Arabia. [38][39][40][41][42][43] In this study, we have assessed the clinical pharmacists' activities during Hajj period. There was a much more demand than other hospitals due to the crowding and increased need for medications.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Besides, the Pharmacist showed a significant clinical outcome for patients care, prevent drug-related problems, and avoid unnecessary additional million US dollars annually. [9][10][11][12][13][14][15][16][17] Besides, the Pharmacist plays vital roles during mass gatherings hajj period annually. [18] All previous pharmacist performances were during the normal situation.…”
Section: Introductionmentioning
confidence: 99%